Simulation of debris flow head movement process in mountainous area based on FLOW-3D - Chaopeng LUO; Ming CHANG; Binbin WU; Peiyuan LIU; Bo YU (Zhongguo dizhi zaihai yu fangzhi xuebao, 2022)
On October 3rd, 2020, a sudden rainstorm in Li County, Aba Prefecture, Sichuan Province. resulted in the outbreak of debris flow in Erjingli gully, which caused severe damage to the highway at the mouth of the gully and blocked the river. To explore the characteristics of the process of debris flow head movement, Erjingli gully was selected as the research object. Through investigation and analysis, the characteristics of the gully source distribution, scale, and morphology were obtained, and the FLOW-3D numerical simulation method was used to analyze the movement characteristics of the debris flow. The different characteristics of the debris flow movement process can be divided into four phases: provenance collection, movement feature mutation, sustainable development and sediment accumulation. It has been proved that the accuracy of this simulation reaches 88.98%. The intensity index was calculated based on the flow velocity and accumulation depth. The debris flow was divided into four grades, and the distribution map was drawn. The extremely high-intensity area accounts for 2.4%, the high-intensity area accounts for 5.1%, the medium intensity area accounts for 13.6%, and the low-intensity area accounts for 78.9%. Based on 3D modeling, the dam is designed to simulate and analyze its effect on debris flow mitigation, which provides a scientific basis for the future control projects.